Evaluasi Kebijakan Pelarangan Impor Pakaian Bekas: Studi Kasus Di Kota Jakarta - Muhammad Azhar Gusti Abdurrafi; Supratiwi Supratiwi (Journal of Politic and Government Studies, 2026)
The importation of used clothing, widely traded through thrifting activities, has grown rapidly in Jakarta amid increasing public demand for affordable fashion. The widespread circulation of imported used clothing threatens the competitiveness of the domestic textile industry, prompting the government to enact a ban through Minister of Trade Regulation No. 40 of 2022, reinforced by Regulation No. 47 of 2025. This study evaluates the policy banning used clothing imports in Jakarta using William N. Dunn's policy evaluation theory, covering six indicators: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. A descriptive qualitative method was employed through in-depth interviews, documentation, and literature review. Informants included the Directorate General of Customs and Excise, the Jakarta Provincial Civil Service Police Unit (Satpol PP), the Indonesian Chamber of Commerce and Industry (KADIN), used clothing traders, and consumers. Findings show that enforcement actions rising from 44 cases (2022) to 192 cases (2024) were not accompanied by reduced circulation, as traders adapted to digital platforms that are difficult to monitor. Supervision suffers from structural inefficiency due to its concentration at formal entry points, while informal distribution channels and digital commerce remain inadequately covered. Based on all six of Dunn's indicators, none are fully met. The policy requires comprehensive reform in its design, digital oversight model, public participation mechanisms, and protection programs for directly affected groups.